THE PHONETIC PHENOMENON OF REDUCTION IN ENGLISH - Khaydarova Nigora; Sotvoldieva Nozimakhon (TADQIQOTLAR, 2025)
Abstract this article discusses the phonetic phenomenon of reduction in the English language, its types, causes, and importance in speech. Reduction plays a significant role in the natural flow of spoken English and contributes to the rhythm and melody of the language.